PHYSICAL EDUCATION AND SOCIAL INTEGRATION OF PRE-SCHOOL ADOLESCENT STUDENTS ON THE AGE FROM 9 TO 12 YEARS OLD, THAT PRESENTPRESENTS SCHOLARY DELAY, ATTENDING “PROGRESSION CLASS” ON DR. MÁRIO AUGUSTO TEIXEIRA DE FREITAS SCHOOL (Fiep Bulletin - online, 2015)
Much even, so many public politics come being developed aiming at to diminish the illiteracy, Brazil present, still, high index how much to this aspect, and it makes difficult the social integration of children, young and adult that live this problem. Such fact is lived deeply by the group of daily daily pay-adolescents, boys and girls of 9 the 12 years old, registered in the "Classroom of Progression" of the Dr. Augusto Mário T. of Freitas School. These beings present  cognitive delay to the intellectual abilities, living deeply, also, adverse circumstances, that cause them difficulty of relationship and inclusion in society. The present article had for objective to show that the Physical Education can consist as a way of social integration of such individuals, since practical its provides the contact between the same ones, representing this the necessary condition for the “life game”, this one contributing for learning in general e, in special, for the learning of proper moral rules to the conviviality in society.
Keywords: pre-school adolescent tudents on the age from 9 to 12 yars old; social integration; Physical Education.